Plagas que atacan las vainas - Schoonhoven, Aart van; Cardona, C. (United Nations Development Programme, 1985)
The biology of pod-attacking insect pests of beans (Apion godmani, Epinotia aporema, Maruca testulalis, and Heliothis spp.) is briefly described. Cultural and chemical control measures are indicated. Some biological control measures are indicated for the case of Heliothis. (CIAT)